Women and power in Hellenistic poetry - Harder, Annette; Klooster, Jacqueline; Regtuit, R. F. (Remco F.); Wakker, G. C. (Hellenistica Groningana, 2021)
"It is a well-known and striking fact that Hellenistic Poetry is full of powerful and powerfully present women, ranging from Ptolemaic and other queens, to female (semi-)divinities and epic heroines. But the Hellenistic era is likewise remarkable for being relatively rich in female authors, specifically in the domain of epigrammatic poetry. This volume sets out to broach not only the question who the powerful women of Hellenistic poetry were, and what their power consisted of, but also, quite emphatically, in what ways they differ from or resemble previous literary representations of women in, for example, Homeric epic, archaic lyric and Athenian tragedy, and why."--Provided by vendor.